Morphological Characterization and Nutritional Evaluation of Sidimpuan Salak (Salacca sumatrana Becc) Based on Flesh Color - Yusnita Wahyuni Silitonga; Irmalia Fitri Siregar; Nasirsah; Nurmaini Ginting; Muhammad Nizar Hanafiah Nasution (Jurnal Penelitian Pendidikan IPA, 2025)
Salak is a native Indonesian plant with various cultivars, one of which is the Sidimpuan salak originating from North Sumatra. Sidimpuan salak fruit has a distinctive taste, namely a fairly sweet but slightly sour taste, sticky, astringent, quite highs water content in the fruit, and various colors of the fruit flesh, namely white, red, and red tinge. This study aims to characterize the morphology of three types of Sidimpuan salak based on the color of the fruit flesh (white, red, red tinge) and compare the glucose content and vitamin C levels of the three types of salak. The method used in this study is a descriptive method and sample determination is done by purposive sampling. Glucose levels are analyzed using a UV-Vis spectrophotometer and vitamin C levels by the idiometry titration method. The results of the study showed that there are differences in morphological appearance between white, red, and red tinge salak. The morphological characteristics of the stems and leaves of red salak rank first, but the size and taste of white salak fruit are superior to red salak. The highest glucose levels were found in white snake fruit samples and the lowest in red snake fruit, while the highest vitamin C levels were found in red snake fruit and the lowest in red snake fruit. Variations in morphology, glucose content, and vitamin C in snake fruit are caused by genetic and environmental factors. The morphological and nutritional differences found in the three types of Sidimpuan snake fruit are predominantly due to genetic factors because the samples were obtained from the same environmental conditions.